Pengaruh Kepemilikan Mangerial dan Kepemilikan institusional Terhadap Managemen Laba Real - Ferdawati, Ferdawati (Jurnal Ekonomi, 2010)
This research is conducted to obtain empirical evidence that there is an influence of managerial ownership and Institutional ownersips on te real earnings management. The sample used in this research is non financial company that listed in Indonesia Stock Excange (ISE) that performs income increasing pattern Period 2004-2008. A Regression is use to test the hypothesis. Hypothetical test result show that managerial ownership is a positive correlation with the real earnings management. However, test result to influence of the institutional ownership on real earnings management was not proofed.